When sexual threat cues shape attitudes toward immigrants: the role of insecurity and benevolent sexism - Sarrasin, Oriane; Fasel, Nicole; Green, Eva G. T.; Helbling, Marc (Frontiers in Psychology, 2015)
Drawing on psychological and political science research on individuals’ sensitivity to threat cues, the present study examines reactions to political posters that depict male immigrants as a sexual danger. We expect anti-immigrant attitudes to be more strongly predicted by feelings of insecurity or representations of men and women as strong and fragile, when individuals are exposed to sexual threat cues than when they are not. Results from two online experiments conducted in Switzerland and Germany largely confirmed these assumptions. Comparing two anti-immigrant posters (general and non-sexual threat vs. sexual threat), Experiment 1 (n = 142) showed that feelings of insecurity were related to an increased support for expelling immigrants from the host country in both cases. However, only in the sexual threat cues condition and among female participants, were perceptions of women as fragile—as measured with benevolent sexism items—related to support for expelling immigrants. Further distinguishing between different forms of violence threat cues, Experiment 2 (n = 181) showed that collective feelings of insecurity were most strongly related to support for expelling immigrants when a male immigrant was presented as a violent criminal. In contrast, benevolent sexist beliefs were related to anti-immigrant stances only when participants were exposed to a depiction of a male immigrant as a rapist. In both cases attitudes were polarized: On the one hand, representations of immigrants as criminals provoked reactance reactions—that is, more positive attitudes—among participants scoring low in insecurity feelings or benevolent sexism. On the other hand, those scoring high in these dimensions expressed slightly more negative attitudes. Overall, by applying social psychological concepts to the study of anti-immigrant political campaigning, the present study demonstrated that individuals are sensitive to specific threat cues in posters.